Oxaliplatin/5-fluorouracil in advanced hepatocellular carcinoma: case report and single-center retrospective review. (October 2014) - Goldstein, Robert; Yu, Dominic; Gillmore, Roopinder; Thirlwell, Christina; O'Donoghue, Pam; Mayer, Astrid; Meyer, Tim
ABSTRACT : Aims: Sorafenib is the only standard therapy for advanced hepatocellular carcinoma, but has a low response rate. Leucovorin and oxaliplatin (FOLFOX) has a superior response rate versus doxorubicin among Asian sorafenib-naive patients. We aimed to retrospectively review the outcome of 20 consecutive patients treated with FOLFOX at a single European center.Materials & methods: Patients had symptomatic disease burdens unlikely to regress with sorafenib or had no proven treatment options (sorafenib-refractory or recurrence post liver transplantation).Results: One sorafenib-refractory patient had a complete response and two liver transplant patients experienced partial responses. Median overall survival was 6.3 months. There was one chemotherapy death due to neutropenic sepsis.Conclusion: In advanced hepatocellular carcinoma, FOLFOX can induce clinically relevant responses, but needs prospective validation.